The Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial dan Leverage Terhadap Manajemen Laba - Suratman, Sasa S; Adha Minaryanti, Annisa; Yuanda, Hilke Dwi Putri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Manager in company with high levels of leverage and high risk, have the possibility to do earnings management to increase the trust of external parties or in this case are investors and the public. This research aims to determine the effect of Institutional Ownership, managerial ownership and Leverage as measured by the debt to asset ratio partially on Real Activity Manipulation and the impact of Real Activity Manipulation on Earnings Management. The research method used is descriptive verification method. The population of this research were 26 food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the 2014-2018. The research sample selection method is based on a purposive sampling method with a total of 9 companies that suit the criteria. Data analysis techniques used in this study are the classic assumption test, multiple linear analysis, simple linear analysis and hypothesis testing. Institutional ownership, managerial ownership, and leverage have no effect on earnings management in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2018 period.